Thr90Ser Mutation in Antithrombin is Associated with Recurrent Thrombosis in a Heterozygous Carrier - Lu, Yeling; Villoutreix, Bruno O.; Biswas, Indranil; Ding, Qiulan; Wang, Xuefeng; Rezaie, Alireza R. (Thrombosis and Haemostasis, 2020)
Antithrombin (AT) is a serine protease inhibitor that regulates the activity of coagulation proteases of both intrinsic and extrinsic pathways. We identified an AT-deficient patient with a heterozygous Thr90Ser (T90S) mutation who experiences recurrent venous thrombosis. To understand the molecular basis of the clotting defect, we expressed AT-T90S in mammalian cells, purified it to homogeneity, and characterized its properties in established kinetics, binding, and coagulation assays. The possible effect of mutation on the AT structure was also evaluated by molecular modeling. Results demonstrate the inhibitory activity of AT-T90S toward thrombin and factor Xa has been impaired three- to fivefold in both the absence and presence of heparin. The affinity of heparin for AT-T90S has been decreased by four- to fivefold. Kinetic analysis revealed the stoichiometry of AT-T90S inhibition of both thrombin and factor Xa has been elevated by three- to fourfold in both the absence and presence of heparin, suggesting that the reactivity of coagulation proteases with AT-T90S has been elevated in the substrate pathway. The anticoagulant activity of AT-T90S has been significantly impaired as analyzed in the AT-deficient plasma supplemented with AT-T90S. The anti-inflammatory effect of AT-T90S was also decreased. Structural analysis predicts the shorter side-chain of Ser in AT-T90S has a destabilizing effect on the structure of AT and/or the AT-protease complex, possibly increasing the size of an internal cavity and altering a hydrogen-bonding network that modulates conformations of the allosterically linked heparin-binding site and reactive center loop of the serpin. This mutational effect increases the reactivity of AT-T90S with coagulation proteases in the substrate pathway.
Keywords: antithrombin; thrombosis; thrombin; factor Xa; stoichiometry